The missing link between job satisfaction and correctional staff behavior: The issue of organizational commitment - Lambert, Eric G. (American journal of criminal justice, 1999)
Over the past twenty years, several empirical studies have examined the consequences of job satisfaction among correctional staff. When looking at worker behavior in other disciplines, though, it is commonplace to include both job satisfaction and organizational commitment. However, very few studies about correctional staff behavior include both concepts. This paper discusses job satisfaction and organizational commitment, and addresses the link between these concepts as it relates to correctional staff attitudes and behaviors. Further, a discussion of measurement issues and recommendations for future research is presented.